STRATEGIC PROSPECTIVE OF VILLA EL SALVADOR FURNITURE CLUSTER - Inche Mitma, Jorge (2006)
This article focuses the next problem: How to formulate a realistic scenery to 2015 and at the same time be the base of a vision that can be carry out to the furniture cluster of Villa El Salvador?; in order to have results, we applied DELPHI and MINI DELPHI surveys as well the prospective strategic method, it involves the MIC MAC, MACTOR and SMIC methods; all the data was processes by shareware software of LIPSOR institute of France. The principal results were: the variables of the strategic axis, the actors role, the bets scenery to 2015 and a vision proposed to that year.